Migrant Tejano Laborers in Wisconsin between 1950 and 1970: Effects of an Exclusionary New Deal - Scott, Sarah J. (My University, 2012)
The Great Depression was a tumultuous period in American history that ushered in an era of tremendous social change in the form of the New Deal. Policies of the era, such as the Wagner Act, formally recognized laborers' rights to organize. Consequently, laborers in the industrial and manufacturing sectors engaged in collective bargaining with the support of the government and strong unions. Their efforts improved working conditions and wages and most laborers began to make up a flourishing middle class in America. However, the Wagner Act did not extend these protections to agricultural workers, who sank further into poverty. This essay focuses on the life and working conditions of migrant Hispanic agricultural workers in Wisconsin between 1950 and 1970. In particular, the paper examines the dangers that these migrants faced while traveling to and from Wisconsin, the inadequate housing the employers provided for them, and the poor wages they received for their labor. This research also includes an examination of the children of migrant workers, child labor, and the lack of education available to them. Based on this analysis, I argue that agricultural laborers' exemption from the Wagner Act resulted in deplorable conditions for migrant agricultural workers in Wisconsin, who were trapped in a cycle of poverty and ethnic discrimination.
Keywords: Agriculture; Labor rights; Wagner Act; Migrant workers; New Deal; Hispanic migrant workers